Making Latino news race, language, class. - Rodriguez, America; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
With this study, America Rodriguez examines news making as part of a larger narrative - the self-creation of a cultural, social and political Latino identity in US culture.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hispanic Americans -- Press coverage -- History; Journalism -- Social aspects -- United States; Hispanic American newspapers -- History; Hispanic American mass media -- History; Hispanic Americans and mass media; Hispanic American journalists; Ethnic press -- United States; Electronic books